Revealing the bonding of solvated Ru complexes with valence-to-core resonant inelastic X-ray scattering. Issue 10 (29th January 2021) - Biasin, Elisa; Nascimento, Daniel R.; Poulter, Benjamin I.; Abraham, Baxter; Kunnus, Kristjan; Garcia-Esparza, Angel T.; Nowak, Stanislaw H.; Kroll, Thomas; Schoenlein, Robert W.; Alonso-Mori, Roberto; Khalil, Munira; Govind, Niranjan; et al.
Abstract : Combined experimental and theoretical Ru 2p4d resonant inelastic X-ray scattering study probes the chemical bonding and the valence excited states of solvated Ru complexes. Abstract : Ru-complexes are widely studied because of their use in biological applications and photoconversion technologies. We reveal novel insights into the chemical bonding of a series of Ru(ii )- and Ru(iii )-complexes by leveraging recent advances in high-energy-resolution tender X-ray spectroscopy and theoretical calculations. We perform Ru 2p4d resonant inelastic X-ray scattering (RIXS) to probe the valence excitations in dilute solvated Ru-complexes. Combining these experiments with a newly developed theoretical approach based on time-dependent density functional theory, we assign the spectral features and quantify the metal–ligand bonding interactions. The valence-to-core RIXS features uniquely identify the metal-centered and charge transfer states and allow extracting the ligand-field splitting for all the complexes. The combined experimental and theoretical approach described here is shown to reliably characterize the ground and excited valence states of Ru complexes, and serve as a basis for future investigations of ruthenium, or other 4d metals active sites, in biological and chemical applications.